Epidemiology and factors associated with acute stress disorder in burned patients: a case-control study (2022)
Introduction A burn injury is a very painful experience, with subsequent emotional problems, which have been gaining relevance to the extent that survival from burns has improved. Among the alterations of the mental sphere in this population is Acute Stress Disorder (ASD) that has been described in up to one-third of patients with major burns. Methodology A nested case-control study was carried out in a cohort of hospitalized patients in a burn referral unit, in patients over 16 years of age. A total of 135 patients, 41 cases, and 94 controls were included. All of them underwent a psychiatric interview, a standardized form was filled out on sociodemographic and clinical information, and the PID-5-BF scale was applied to evaluate associated personality elements. The diagnosis of acute stress was made with the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria. Results The incidence of acute stress was 23.4%. When the clinical and sociodemographic characteristics of both the cases and the controls were compared, the risk factors were subsidized insurance, flame burn, burn in a special area, third-degree burn, high pain, stay in the Intensive Care Unit (ICU), peritraumatic amnesia and life threat. Patients also had a higher percentage of burned body surface, higher average pulse, longer hospital length of stay, higher average in the negative affect variable and in the psychoticism variable of the PID-5-BF scale. But for the multivariate analysis using logistic regression, the model that best explains the presence of acute stress only includes the variables life threat (Odds Ratio adjusted (ORa): 117.0; Confidence Interval (CI): 10.9–1258.5), severe pain (ORa: 9.9; CI: 1.8–52.8), electrical burn (ORa: 20.8; CI: 17.2–250), burn in a special area (ORa: 8.9; CI: 1, 0–76.8), third-degree burn (ORa: 10.4; CI: 0.7–166.7). Conclusion Acute stress disorder is frequent in the hospitalised burn population, and is more frequent than in other types of trauma. Associated factors with the presentation of Acute Stress Disorder are the feeling of life threat at the time of the burn, having pain classified as strong (Visual Analog Scale (VAS) 5–10), electrical burn, and burns in special areas.